Persepsi Guru Pendidikan Pancasila Terhadap Pemanfaatan Artificial Intelligence Sebagai Upaya Meningkatkan Social Responsibility di SMAN Colomadu Tahun 2025/2026 - Dini Pramudita Fatika Sari; Trisiana, Anita; Sutoyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objectives of this study were to describe the utilization of Artificial Intelligence (AI) in learning based on the perceptions of Civics (PPKn) and to analyze the influence of Artificial Intelligence (AI) utilization in Civics learning on strengthening students social responsibility.This research employed a qualitative approach with a descriptive interpretative research design. Data were obtained from primary and secondary sources through observation, interviews, and documentation. The validity of the data was ensured through source and technique triangulation. Data analysis was conducted through several stages, including data collection, reduction, presentation, and conclusion drawing. The results of this study be concluded that civics teachers perceived the utilization of Artificial Intelligence (AI), particularly ChatGPT, as a learning support tool that assists in lesson planning and material enrichment, without replacing the essential role of teachers as the main educators in guiding and shaping students character and the utilization of AI in Civics learning had an influence on strengthening students’ social responsibility, especially in terms of social awareness and understanding. Students showed better comprehension of social issues and civic responsibilities; however, this influence had not been fully reflected in consistent changes in students’ social attitudes and behaviors. The development of empathy, social concern, and responsibility still requires continuous teacher guidance, experiential learning activities, and support from the school environment and families. Keywords: Teacher Perception, Artificial Intelligence, Civics Learning, Social Responsibility